Protein nanosphere anchors for stabilizing hydroxylated polymer chains in organic memory transistors with outstanding retention characteristics - Seo, J; Kim, H; Lee, C; Kim, C (Wiley, 2020)
It is demonstrated that a heme protein (cytochrome c [Cyt c]) nanosphere plays a strong anchoring role in binding hydroxyl groups of poly(vinyl alcohol) (PVA) leading to outstanding high‐temperature (100 °C) retention characteristics of transistor‐type organic memory devices (TOMDs). The PVA:Cyt c layers are spin‐coated on indium tin oxide gate electrodes from aqueous solutions with various Cyt c contents up to 50 wt%, followed by the formation of poly(3‐hexylthiophene) (P3HT) channel layers and nickel/aluminum top source/drain electrodes in TOMDs. Results show that adding 20 wt% Cyt c improves the drain current of devices in the presence of good hysteresis characteristics, which are maintained even after exposure to high‐temperature conditions (100 °C). The excellent conservation of hysteresis characteristics is attributed to the formation of Cyt c nanospheres that act as an anchoring point to retard the relaxation of PVA chains via specific interactions (hydrogen bonding etc.) between amino groups in the Cyt c nanosphere surfaces and hydroxyl groups in the PVA chains. The optimized PVA:Cyt c layers (20 wt% Cyt c, thermal treatment at 100 °C) deliver excellent retention characteristics to TOMDs, whereas no memory function is measured in the case of the pristine PVA layers at 100 °C.